Rethinking Da‘wah Strategy as a Basis for Mitigating Conflict Involving Muslim Minorities: Insights from Bali and Peniwen Malang, Indonesia - Al Turki, Usamah; Kholish, Moh. Anas; Jamal, Jamal; Tohari, Ilham (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2025)
This article examines inclusive da‘wah models in the context of Muslim minority communities in Bali and Peniwen, Indonesia. In Bali, the Muslim minority community peacefully coexists with the Hindu majority community, which dominates local customs and morals. On the other hand, the Muslim minority community in Peniwen is situated in a Christian-majority environment that has a long history of inter-religious tensions. This study examines how da‘wah dynamics operate in specific contexts and analyzes the role of da‘wah in interfaith relations. Through a qualitative case study approach, this research collected data through in-depth interviews, participatory observation, and document analysis involving religious leaders, da‘wah activists, and interfaith community members. The findings indicate that inclusive da‘wah based on dialogue, cooperation, and cultural sensitivity significantly contributes to strengthening social cohesion between the religious communities. In Bali, the value of ‘Islam as a mercy to the world’ contextualized with the principle of Tri Hita Karana has successfully built harmonious interfaith collaboration. In Peniwen, a participatory approach has fostered interfaith solidarity in response to social challenges. This study offers a transformative da‘wah model relevant to minority Muslim communities and makes concrete contributions to the formation of a just, peaceful, and mutually respectful multicultural society.